Metabolic fingerprinting of chorionic villous samples in normal pregnancy and chromosomal disorders. (1st July 2019) - Murgia, Federica; Iuculano, Ambra; Peddes, Cristina; Santoru, Maria Laura; Tronci, Laura; Deiana, Monica; Atzori, Luigi; Monni, Giovanni
Abstract: Objective: Placenta‐related biological samples are used in biomedical research to investigate placental development. Metabolomics represents a promising approach for studying placental metabolism in an effort to explain physiological and pathological mechanisms. The aim of this study was to investigate metabolic changes in chorionic villi during the first trimester of pregnancy in euploid and aneuploid cases. Methods: Samples from 21 women (13 euploid and eight aneuploid) were analyzed with 1 H‐nuclear magnetic resonance (NMR), gas chromatography–mass spectrometry (GC‐MS), and high‐performance liquid chromatography (HPLC). Multivariate statistical analysis was performed, and differences in metabolites were used to identify the altered metabolic pathways. Results: A regression model to test the correlation between fetal crown‐rump length (CRL) and metabolic profile of chorionic villi was performed in euploid pregnancies ( R 2 was 0.69 for the NMR analysis and 0.94 for the GC‐MS analysis). Supervised analysis was used to compare chorionic villi of euploid and aneuploid fetuses (NMR: R 2 X = 0.70, R 2 Y = 0.65, Q 2 = 0.30, R 2 X = 0.62; GC‐MS: R 2 Y = 0.704, Q 2 = 0.444). Polyol pathways, myo‐inositol, and oxidative stress seem to have a fundamental role in euploid and aneuploid pregnancies. Conclusion: Polyol pathways may have a crucial role in energy production in early pregnancy. Excessive activation in aneuploid pregnancies may lead to increased oxidative stress. Metabolomics represents a promising approach to investigate placental metabolic changes. Abstract : What's already known about this topic? Currently, there are few studies that evidence specific changes of the placental metabolic profile during the first trimester of pregnancy. This study analyzes alterations in placental metabolites composition in euploid and aneuploid cases. Polyols might have a crucial role in energy production. In aneuploid cases, the exceeding activation of polyol pathway leads to the increase of oxidative stress. Myo‐inositol and cholesterol decrease in cases of aneuploidy.